2017
DOI: 10.3892/mmr.2017.7576
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol exerts potential activities to inhibit the growth, migration and invasion of human gastric cancer BGC823 cells via downregulating MMP-2 and MMP-9

Abstract: Paeonol (Pae) is an herbal extract that has attracted extensive attention for its anti-cancer effects demonstrated by a number of studies, which have predominantly demonstrated inhibition of cell proliferation and induction of apoptosis. The influence of Pae on cancer cell metastasis has been less widely reported. The present study aimed to investigate the under-reported effects of Pae on the growth, invasion and migration of poorly differentiated BGC823 gastric cancer cells with strong invasive and metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…MMPs, known as proteolytic enzymes, were previously reported to be associated with tumor metastasis and invasion (45,46). Additionally, MMP9, an extracellular matrix-degrading enzyme, serves a role in metastasis and invasion of carcinoma cells (47,48). MMP9 was identified as a modulatory target of N-cadherin-dependent signaling (23).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs, known as proteolytic enzymes, were previously reported to be associated with tumor metastasis and invasion (45,46). Additionally, MMP9, an extracellular matrix-degrading enzyme, serves a role in metastasis and invasion of carcinoma cells (47,48). MMP9 was identified as a modulatory target of N-cadherin-dependent signaling (23).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Furthermore, previous studies have shown that Paeonol inhibits invasion and migration of gastric cancer cells by down-regulating the MMPs. 9 However, the anti-metastatic effects of Paeonol, especially in PDAC, lack conclusive evidence. In the absence of other known studies on the anti-migration and anti-invasion activities of Paeonol, we aim to further investigate the activities of Paeonol on migration and invasion and its underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Previous studies suggested that Paeonol possesses anti-proliferation, apoptosis induction, and cell cycle arresting effects in various types of cancers, such as breast, colorectal, lung, ovarian, gastric cancer, etc. 9,[12][13][14][15][16][17][18][19][20][21] More recent studies reported that Paeonol enhanced paclitaxel-induced apoptosis in breast cancer cells, 20,22 reversed Doxorubicin resistance in liver cancer, 23 and enhanced the radiosensitivity of lung cancer cells. 24 Studies also reported the anti-metastatic activities of Paeonol in human fibrosarcoma, chondrosarcoma and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of CM, the potential anticancer effect of Cynanchum paniculatum can be ascribed to one of the CM traits by clearing wind-damp or removing toxicity. Despite the lack of direct claims to the anticancer properties of Cynanchum paniculatum, the link between anticancer and anti-inflammation can be established after anti-inflammation, anticachectic, antioxidant, antiproliferation, and antiinvasion properties [99][100][101][102][103].…”
Section: Malignant Diseasesmentioning
confidence: 99%